The Role of Notaries in Translating Deeds for Applicants Who Do Not Master Indonesian - Sugiarto, Dinda Putri; Sulistyandari, Sulistyandari (JIHAD : Jurnal Ilmu Hukum dan Administrasi, 2025)
A notary is a public official who has the authority to draft authentic deeds and carry out other notarial functions as regulated in Law Number 2 of 2014 concerning the Position of Notary. One of the key responsibilities of a notary is to ensure that all appearing parties fully understand the content and intent of the deed being executed. This obligation becomes particularly important when a party does not understand the Indonesian language. Article 43 of the Notary Law explicitly stipulates that the notary must translate or explain the content of the deed to the appearing party in a language they understand, and if unable to do so, the notary is required to involve an official translator. This duty reflects not only the legal, ethical, and administrative responsibilities of the notary but also embodies the principles of justice and legal protection for all parties involved. This research employs a normative juridical method with a statutory and conceptual approach, utilizing primary, secondary, and tertiary legal materials. The findings indicate that the notary's responsibility to translate the contents of a deed is crucial for preserving the validity and evidentiary strength of an authentic deed. Failure to fulfill this obligation can result in the deed losing its authenticity and may lead to civil, administrative, and even criminal liability for the notary. Furthermore, the failure to translate the deed may constitute a breach of professional ethics, thereby undermining the integrity and public trust in the notarial profession.